Efficacy and Safety of Peroral Endoscopic Myotomy in the Treatment of Zenker’s Diverticulum: A Single-Center Experience - Buyruk, Abdullah Murat; Erdoğan, Çağdaş (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The efficacy and safety of Zenker’s peroral endoscopic myotomy (Z-POEM), a current method in the treatment of Zenker’s diverticulum (ZD), have been demonstrated in a limited number of studies and case reports. This study aimed to report our experience with the Z-POEM method. Materials and Methods: Patients with ZD who were treated with Z-POEM between January 2019 and March 2023 and had a followup period of at least 3 months were included in the study. Our primary endpoint was clinical success. A Kothari–Haber score (KHS) of 2 or less at 1 month postoperatively was defined as clinical success. Our secondary endpoints were adverse events and recurrence rates. Results: In total, 20 patients (males, 65%; mean age, 63 ± 14.4 years) were treated with Z-POEM. The mean ZD septum length was 33.7 (±11.04) mm. The technical success rate was 100% (20/20), and the clinical success rate was 95% (19/20). In 1 case with a large ZD (septum length of 60 mm), the mucosal septum, which was thought to cause partial persistence of symptoms, was treated by endoscopic septotomy. The mean KHS decreased significantly after Z-POEM (preoperative KHS: 7.3 and postoperative KHS: 0.15, P < .0001). The median follow-up period was 10 months (interquartile range, 3-39). No recurrence was observed in any case. Intraprocedural mild subcutaneous emphysema was observed in 4 (20%) cases. Emphysema regressed spontaneously in the postoperative period without any treatment. Conclusion: Zenker’s peroral endoscopic myotomy is a successful and reliable method in the treatment of ZD, with low recurrence rates. Cite this article as: Buyruk AM, Erdoğan Ç. Efficacy and safety of peroral endoscopic myotomy in the treatment of Zenker’s diverticulum: A single-center experience. Turk J Gastroenterol. 2024;35(2):119-124.